Problem of Authority For Executing Task (PLT) In The Transitional Period of Regional Government Before and After The Simultaneous Elections Based On Law Number 23 Of 2014 Concerning Local Government - Rona Indara (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The task executor (PLT) in state administration is an official who occupies a temporary position because the official who occupied that position was previously unable to or was subject to legal regulations so that he did not occupy that position. The purpose of this research is to describe the appointment of the PLT if there is a vacancy in the regional head position during the transition period, analyze, qualifications, limits of the PLT authority and strategic policies during the transition period, but are still held by the PLT and know and analyze the sanctions given to the PLT who does something outside authority. The method used in this scientific work is a normative and qualitative juridical research method that is studied holistically, contextually, progressively, it is known that a. The appointment of Acting Governors is appointed by the President through a proposal from the Minister of Home Affairs, while the appointment of Regents/Mayors is appointed by the Minister of Home Affairs through a proposal by the Governor. b. The qualifications of the PLT who were appointed based on Law Number 8 of 2015 article 201 paragraph (8) to fill the vacancy for the position of Governor are from middle high leadership positions. b. If during the change period a strategic policy is needed that must be taken by the acting head, then it is regulated by Article 132 A paragraph (2) Government Regulation Number 49 of 2008 concerning the Third Amendment to Government Regulation Number 6 of 2005 concerning Election, Ratification of Appointment and Dismissal of Regional Heads and Deputy Regional Head, which must be approved by the Minister of Home Affairs. c. In fact, there are no clear provisions for the Plt who abuses his authority, as the type of authority given to the PLT is unclear.